1997
DOI: 10.1159/000237681
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Azelastine on the Infiltration of Inflammatory Cells into the Bronchial Mucosa and Clinical Changes in Patients with Bronchial Asthma

Abstract: Background: Azelastine is an oral antiallergic compound but there is no direct evidence of its anti-inflammatory actions in bronchial asthma. We examined the effect of azelastine on inflammatory cells infiltrating the bronchial mucosa and clinical symptoms in atopic asthma in a double-blind, parallel, randomized study. Methods: The study was completed by 13 subjects in the azelastine (4 mg/day) group and 11 subjects in the placebo group. Treatments were randomly administered for 3 months. Each subject recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…However, azelastine, although classified as a basic compound along with terfenadine, inhibited both IPR and LPR. In addition to the inhibition of mediator production and release, azelastine has been shown to inhibit the generation of superoxide from activated neutrophils [5], and to reduce the infiltration of eosinophils and activated T lymphocytes into the bronchial mucosa in patients with asthma [12]. Azelastineinduced inhibition of LPR may be partly associated with the direct effect against inflammatory cells, although the precise mechanism remains to be examined in detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, azelastine, although classified as a basic compound along with terfenadine, inhibited both IPR and LPR. In addition to the inhibition of mediator production and release, azelastine has been shown to inhibit the generation of superoxide from activated neutrophils [5], and to reduce the infiltration of eosinophils and activated T lymphocytes into the bronchial mucosa in patients with asthma [12]. Azelastineinduced inhibition of LPR may be partly associated with the direct effect against inflammatory cells, although the precise mechanism remains to be examined in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Of the new generation of H 1 receptor antagonists, topical azelastine has been shown to be a powerful topical antihistamine, decreasing eosinophils and T lymphocyte activation 108. It both reduces and prevents the symptoms of SAC,109 but does not appear to reach maximal activity for 7 days 110.…”
Section: Treatment Options and Regimensmentioning
confidence: 99%
“…A similar study also concluded that cetirizine could prevent exacerbation of seasonal pollen asthma (48). Azelastine treatment of 13 asthmatic patients resulted in significant improvement in asthma symptoms accompanied by a reduction in activated eosinophils and T lymphocytes in the bronchial mucosa compared with the placebo‐treated group (49), while another study found that azelastine reduced the need for inhaled corticosteroids in patients with chronic bronchial asthma (50). In addition, azelastine treatment of patients with chronic asthma resulted in rapid onset of bronchodilating activity, as demonstrated by a statistically significant mean percentage improvement in FEV 1 (51).…”
Section: Antihistamines: Anti‐inflammatory Effects In Vivomentioning
confidence: 83%